2020
DOI: 10.1016/j.amsu.2020.08.007
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and paediatric dentistry- traversing the challenges. A narrative review

Abstract: The coronavirus disease (COVID-19) pandemic has become a major global public health emergency with a focus on preventing the spread of this virus for controlling this crisis. A dental setting is at a high risk of cross infection amid patients and dental practitioner's owing to the spread of infection via droplets suspended in the air by infected symptomatic or asymptomatic subjects. This review article informs about measures which reduce facility risk, manage symptomatic patients and protect personal health ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 14 publications
0
11
0
7
Order By: Relevance
“…In the literature, it has been indicated that aerosols and high-speed hand piece have the potential to spread bacteria and viruses to the dentist and dental staff (Barabari and Moharamzadeh 2020 ; Shah 2020 ; Checchi et al 2020 ). So, choosing hand instruments or low-speed hand piece by most of the participants for dental management of suspected COVID patient indicated their awareness about the role of aerosols in spreading of the viral infection and that proper dental management for a suspected COVID patient is preferred to be by hand instruments.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, it has been indicated that aerosols and high-speed hand piece have the potential to spread bacteria and viruses to the dentist and dental staff (Barabari and Moharamzadeh 2020 ; Shah 2020 ; Checchi et al 2020 ). So, choosing hand instruments or low-speed hand piece by most of the participants for dental management of suspected COVID patient indicated their awareness about the role of aerosols in spreading of the viral infection and that proper dental management for a suspected COVID patient is preferred to be by hand instruments.…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic outbreak of COVID-19 has modified the training approaches (didactic and clinical) in dentistry for the subsequent years, intending to reduce transmission of COVID-19 infection (12,14). There were cancellation of some conferences and postponement of some due to the present outbreak of COVID-19 disease (Table 1) 1,2,3,4,5,6 . However, the COVID-19 disease outbreak provided new paths for dental students' exposure to research.…”
Section: Canceled Meetingsmentioning
confidence: 99%
“…A responsável legal do paciente assinou um termo de consentimento livre e esclarecido autorizando a realização do tratamento e a divulgação de informações e imagens referentes ao caso clínico. cárie dentária visando a redução ou eliminação da geração de aerossol 1,2,7,12 , estímulo às atividades educativas e de promoção de saúde e recomendação, ainda mais rigorosa, do uso de equipamentos de proteção individual 4,19 . A adequação a essas recomendações é um desafio na prática odontológica, tanto nos consultórios quanto nas clínicas das instituições de ensino superior.…”
Section: Relato Do Casounclassified
“…Publicações nacionais e internacionais recomendam que o manejo da cárie dentária seja realizado usando procedimentos minimamente invasivos [1][2][3][4] . Essa abordagem envolve procedimentos não invasivos, como o controle do biofilme, da dieta e da mineralização das estruturas dentárias; e outros micro invasivos e invasivos, como a aplicação de selantes e as restaurações, respectivamente, que têm o objetivo de preservar, ao máximo a estrutura dentária e gerar condições favoráveis para a remineralização dos tecidos 5 .…”
Section: Introductionunclassified